Split leap with and without ball performance factors in rhythmic gymnastics - Mkaouer, B.; Amara, S.; Tabka, Z. (Science of Gymnastics Journal, 2012)
In rhythmic gymnastics execution quality depends directly on the level of technical expertise, as well as physical performance of the gymnast. the objective was to study the variation of execution factors, particularly the strength, speed and flexibility when performing gymnastics` jumps split leap with and without throw-catch the ball. Five female gymnasts aged 12 to 15 years members of Tunisian national team of rhythmic gymnastics participated in this study. Every gymnast realized the split leap four times without apparatus and with apparatus. 2D motion analysis has been established to study the split leap with and without throw-catch the ball. The results show a significant variation of execution factors when introducing the apparatus such as the initial velocity, vertical displacement, the fly time, the component of vertical and horizontal force and the angular velocity of the split. When performing the split leap with apparatus, execution parameters show a significant decrease with the exception of the vertical velocity, acceleration and angular velocity of the split, which increase to compensate for the fall signs of strength and vertical displacement. Finally, the results showed also that probably gymnasts did not perform a jump with apparatus the best way that could.